Relationship between degree of P2Y12 receptor blockade and inhibition of P2Y12-mediated platelet function - Judge, Heather M.; Buckland, Robert J.; Sugidachi, Atsuhiro; Jakubowski, Joseph A.; Storey, Robert F. (Thrombosis and Haemostasis, 2010)
The thienopyridine P2Y12 receptor antagonists clopidogrel and prasugrel prevent arterial thrombosis and are routinely used following percutaneous coronary intervention. However, the optimal level of P2Y12 blockade to effectively inhibit platelet function is unknown. These studies utilised the active metabolite of prasugrel (R-138727) to achieve a range of P2Y12 blockade in vitro and assessed several aspects of platelet function. Blood from healthy volunteers was incubated with R-138727 (0–10 μM). P2Y12 receptor number was assessed using a 33P-2MeSADP binding assay. Platelet aggregation (PA) was measured by optical aggregometry with ADP 2–20 μM. VASP phosphorylation, annexin V binding, microparticle formation and P-selectin expression were assessed by flow cytometry. Increasing numbers of unblocked receptors were required for a sustained aggregation response with decreasing concentrations of ADP. A P2Y12 receptor blockade of 60–80% resulted in strong inhibition of final PA response, P-selectin expression, microparticle formation and vasodilator-stimulated phosphoprotein (VASP). PA induced by ADP 2 μM and P-selectin expression were particularly sensitive to low levels of receptor blockade whereas the VASP phosphorylation assay was relatively insensitive, requiring 60% receptor blockade to achieve substantial inhibition. Different assays varied in their ability to discriminate particular ranges of P2Y12 blockade and 80% or greater P2Y12 receptor blockade is required for consistently strong inhibition of several aspects of platelet function. These data guide the interpretation of results from different assays used to monitor the effects of P2Y12 receptor antagonists.
Keywords: Platelet; P2Y12; thienopyridines; receptor blockade; ADP